Entrevista com Cedric Boeckx (Catalan Institute for Advanced Studies & Universitat Autònoma de Barcelona) - Boeckx, Cedric; Veloso, João; Martins, Pedro Tiago (elingUP: Revista Eletrónica de Linguística dos Estudantes da Universidade do Porto, 2017)
Cedric Boeckx is a Research Professor at the Catalan Institute for Advanced Studies (ICREA), and a member of the Center for Theoretical Linguistics at the Universitat Autònoma de Barcelona. Most recently he was an Associate Professor of Linguistics at Harvard University. He is the author and editor of various books on syntax, minimalism and language (from a biolinguistic perspective). He is also the founding co-editor, with Kleanthes K. Grohmann, of the Open Access journal Biolinguistics. The interview came to fruition after we had the idea of asking various linguists the following question: "What is the right place for linguistics?". At first, we were looking for short, straightforward answers. The question soon proved to be hard to approach that way, and Prof. Cedric Boeckx was kind enough to accept our invitation for a more thorough elaboration on the subject, under the "Interview" section of our journal, which he generously granted us on November 7th, 2011, at the Faculty of Letters of the University of Porto, a day before his "Introduction to Biolinguistics" workshop, also there, and for which we are also very thankful. This text is a virtually word-for-word transcription of the recorded 2-hour long interview, subject only to minor revisions by our editorial team and some comments by the interviewee. We hope that the final result is of interest to students, researchers and people alike.